The dilemma of using flat vs. clip pedals since early ages in BMX cycling: Influence of age and previous experience - Romero-Rodriguez, R.C.; Mateo-March, M.; Zabala, M. (Science & Sports, 2013)
Introduction: It is widely recognized that clip pedals (CP) in BMX cycling may improve sprinting performance, but there is not a consensus about when to start using them or if its use should be related to subjects` specific age, or physical and technical level. The aim of this study was to demonstrate the effects on performance in sprint acceleration of CP above the normal flats pedals (FP), and to observe whether variables such as subjects` experience, age, or category level determine these effects. Synthesis of the facts: Although a significant improvement was found in sprinting time by using CP vs. FP (P < 0.05), the results showed no significant differences for this average gain between groups due to variables as age, experience, physical or technical level, or ranking (P > 0.32). Conclusions: The main conclusions of this study are that: the use of CP improves performance in the sprint of BMX cycling discipline; and that this improvement is independent of subjects` age, experience, physical or technical level, and ranking.